Strategi Penguatan UMKM Melalui Pelatihan Pemasaran Digital Berbasis Pemasaran Syari’ah: Studi pada Dinas Koperasi Bagian UMKM Kabupaten Bungo - Risa Sukmaya; Busriadi Busriadi; Nayla Wulandani; Misbahun Nur Fadhillah; Amar Dandi Pratama; Yurhasni Putri (khidmatan, 2026)
Micro, Small, and Medium Enterprises (UMKM) are a strategic sector in both regional and national economic development. However, UMKM actors still face challenges in marketing, especially in implementing sharia-based ethical marketing principles. This study aims to analyze the strategy of the Department of Cooperatives for UMKM Affairs of Bungo Regency in strengthening UMKM actors’ capacity through sharia-based digital marketing training. The activity involved approximately 30–40 UMKM actors registered at the UMKM Clinic of Bungo Regency as the target partners. The research uses a descriptive qualitative approach with data obtained from in-depth interviews with the Head of the Division of Cooperatives and UMKM. Data analysis followed the interactive model of Miles and Huberman, covering a preparation stage (needs identification and material development), an implementation stage (practical digital marketing workshop integrating Islamic values), and an evaluation and monitoring stage (participant feedback and planned follow-up coaching clinic). The results show that the training enhanced UMKM actors’ understanding and ethics in digital business according to sharia principles, promoting business transformation towards sustainable Islamic economic growth.